Comunidades tradicionais quilombolas do nordeste de Goiás: quintais como expressões territoriais - Maria Geralda de Almeida (Confins)
Quilombola communities at northeastern Goias, known as Kalunga, contribute to the maintenance of the regional savannah, Cerrado. It’s understood that these communities, because of their culture and territoriality, interact with nature and mediate their relations with the world in a manner that builds up a particular way of life. We exemplify with the ‘Kalunga backyards’ as “culturalized territory”. They hold a Kalunga cultural identity. Based on participant observation and interviews with the Kalunga, following qualitative methodological approach, as the means to understand their socioterritorial organization of backyards, their uses and new uses to and for tourism. Even though the Kalunga live in a Cerrado region, their backyards usually don’t have plants of this biome.